Rubmacula, a new leafhopper genus from China (Hemiptera: Cicadellidae: Deltocephalinae) - Cheng, Mengsha; Zhang, Lan; Xing, Jichun (Zootaxa, 2025)
A new leafhopper genus from China, Rubmacula gen. nov., with R. lvchunensis sp. nov. as type species is described and illustrated. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).